Consumer health informatics: ethics, evaluation and standards - Berner, Eta S.; Singh Sandhu, Amarinder; Goodman, Kenneth W. (Acta Bioethica, 2005)
This article discusses the ethical issues involved in consumer health informatics -specifically those issues surrounding the provision of medical information for patients on the World Wide Web. The discussion includes concerns and suggestions relating to: quality control and error avoidance, Internet governance and Web site responsibility, and intellectual property and control. These issues are argued to be of exceptional importance in the developing world, including Latin America and the Caribbean.